PERGOLAKAN POLITIK ANTARA PEMERINTAH SIPIL DAN TNI AD DI INDONESIA PADA MASA PEMERINTAHAN PRESIDEN SOEKARNO - Ilham Galih Pambudi; Octavian Hendra Priyatno; Fitri Mardiani; Dewicca Fatma Nadilla (Prabayaksa: Journal of History Education, 2025)
The army is one of the dimensions of the TNI that is actively involved in civil administration. Disagreements between army leaders and civilian government regarding authority and command have been a persistent source of tension between civil groups and the military. The purpose of this study is to examine: 1) The July 3rd, 1946 Incident, 2) The October 17th, 1952 Incident, and 3) The Charter on the Integrity of the Army. This research employs critical historical methods. The research process begins with topic selection as an initial activity to determine the problem to be examined. The second phase involves collecting sources from archives, newspapers, and books. These sources were obtained from various locations including the National Archives of the Republic of Indonesia, UNY Library, Jogja Library Center, and the National Library. The third phase is verification, also called source criticism, to ensure the validity of the sources. The fourth phase is interpretation, which involves analyzing the sources. The fifth phase is historiography, which presents the research results. This research demonstrates that: (1) The Army (AD) had strong supporting factors for political involvement since the Proclamation of August 17, 1945; (2) The July 3rd, 1946 Incident and the October 17th, 1952 Incident indicate that relations between civilian and military groups were strained; (3) The Army Charter became a symbol of reunification following internal divisions within the Army.